Visualization of the Synthetic Environment Data Representation & Interchange Specification data for verifying large-scale synthetic environment data. (October 2015) - Kang, Yuna; Kim, Hyunki; Han, Soonhung
The need for reusing synthetic environment data that are employed in the field of modeling and simulation has recently been rising. SEDRIS (Synthetic Environment Data Representation & Interchange Specification) is a standard to exchange synthetic environment data, and is the specification utilized in various military simulations of the Pentagon for representing and exchanging three-dimensional data. SEDRIS represents environmental areas based on a data model; it can represent wind speed, wind directions, weather changes, and the information of buildings, as well as terrain data. In some situations, however, the synthetic environment data stored in SEDRIS format should be converted to various visualization formats. Firstly, because SEDRIS is a form of a super-set, it is necessary to verify whether large-scale SEDRIS files are stored successfully through visualization. In addition, the synthetic environment data should be visualized in some visualization programs for the simulation results to provide an immersive and realistic sense. In this study, we suggest several methods for visualizing synthetic environmental data stored in the SEDRIS format. We developed the converters for converting SEDRIS to the several visualization formats and developed the direct visualization programs using an open-source visualization engine. These results allow us to visualize the stored SEDRIS file and to verify whether the saving stage with native data is performed normally or not.